Teachers’ learning at schools: developing pedagogical capacity for curriculum design trhough co-teaching | cogenerative dialogue - El Kadri, Michele Salles (Acta Scientiarum. Education, 2020)
This article aims at discussing development in an experience of engaging teachers and students in the design of the curriculum at a public school. It is grounded on a socio-historical perspective of learning and in (coteaching | cogenerative dialogue) as a theorethical-methodological approach. Data was gathered in a two-year project through interactions meetings at schools and analyzed through critical discourse analysis (transitivity) and conversational analysis. The results of the study point out that having had the opportunity to interact in co-plannings and redesigning the curriculum, new attitudes emerged. Furthermore, participating in more democratic spaces and being able to redesign their own curricula during teaching practicum had effects on how the participants perceive the participation of high school students. It is concluded that developing teachers’ pedagogical capacity for curriculum design may influence the degree to which teachers engage in a principled, reform-oriented analysis when creating learning opportunities for students.